Psycho-Oncology: Array - Munteanu (Moisă), Valentina-Beatrice (New Trends in Psychology, 2021)
Cancer is a concept that refers to an accumulation of abnormal cells that grow and spread in certain situations in the body. The presence of genetic abnormalities that spread cancer and which are acquired incidentally due to errors in DNA replication that can be inherited genetically, and present in the cells of birth. Cognitive patterns, different mental representations according to their experience that the patient has related to the disease modified by psychological reactions to the diagnosis of cancer, cognitive factors are major causes of the psychological response. People have reactions to an incident / news, in certain circumstances, according to their personal way of interpretation, trying to explain and find answers, giving meaning to the current situation. With the increase of awareness and association of psychological factors with cancer and its treatment have led to an increase in the number of supportive interventions for both patients and their families. They can benefit from both traditional approaches such as psychotherapy, but also from melotherapy, aromatherapy, relaxation techniques, yoga. Over time, it has been found that patients who benefit from psychological intervention have lower levels of depression, anxiety and a considerable improvement in mental and emotional health, thus decreasing morbidity and increasing the quality of life in patients diagnosed. recently with cancer, you are being treated.